A Geophysical Study of Central Kyparissiakos Gulf Coastal Dune Field (Ionian Sea, Greece) - Mitsika, G.S.; Alexopoulos, J.D.; Giannopoulos, I.K.; Gkosios, V; Poulos, S. (Near Surface Geoscience 2023 - 29th European Meeting of Environmental and Engineering Geophysics, 2023)
The coastal environment of central Kyparissiakos Gulf, located at the west coast of Peloponnesus, Greece, comprises of a sandy beach associated with an extended dune field at its backshore area. This area is characterized as an essentially tideless coastal environment exposed to high wave activity. Regarding the identification, the thickness and characteristics of the uppermost substratum of the selected coastal site a detailed geophysical research was carried out. The geophysical survey aims to determine the thickness and the characteristics of the upper substratum of the selected coastal area, leading to the quantification of the sediment budget; the latter is considered essential to address potential coastal erosion. For this reason, the geophysical techniques of Electrical Resistivity Tomography (ERT) and Ground Penetrating Radar (GPR) were implemented to profiles normal and parallel to the shoreline. The geophysical results reveal the presence of the interface between the dry and wet sand deposits, along with the structure and the downward extension of the sandy material.